Media, myth and terrorism : a discourse-mythological analysis of the 'blitz spirit' in British newspaper responses to the July 7th Bombings /: a discourse-mythological analysis of the 'blitz spirit' in British newspaper responses to the July 7th Bombings. (2015) - Kelsey, Darren, 1983-
No abstract available